Compensation for subjects of medical research: the moral rights of patients and the power of research ethics committees. - Guest, S (1997)
Awareness of the morally significant distinction between research and innovative therapy reveals serious gaps in the legal provision for compensation in the UK for injured subjects of medical research. Major problems are limitations inherent in negligence actions and a culture that emphasises indemnifying researchers before compensating victims. Medical research morally requires compensation on a no-fault basis even where there is proper consent on the part of the research subject. In particular, for drug research, there is insufficient provision in the current patient guidelines of the Association of the British Pharmaceutical Industry, since they make "no legal commitment" to paying compensation for injury to patient subjects. There is a need for the provision of both adequate insurance and contractual arrangements for making payments. The solution is for Local Research Ethics Committees (LRECs) to make use of their power to withhold approval of medical research where compensation is not legally enforceable.